Hubungan Derajat Nyeri Dengan Kualitas Hidup Pasien Osteoartritis Di Poli Syaraf Rumah Sakit Umum Daerah Dr. Hardjono Ponorogo - Amanda, Thiar Theria; , dr. Listyo Asist Pujarini, M.Sc, Sp.S; , dr. D. Dewi Nirlawati (2015)
Background: Osteoarthritis is a disease involved degeneration of the joint cartilage, joint lining, ligament, and bone that caused pain and stiffness. Degeneration, ischemic, and necrosis caused pain in joint that caused limitation of motion, decrease in strength and muscle balance, dificulties and limitation in activities that lead to decreased or impaired quality of life (QoL). Measured Quality of Life need to be done for evaluate the body condition in every person. The degree of pain can be assessed used Numerical Rating Scales (NRS) score, whereas quality of life assessed used SF-36 score. This study for knowing assosiation the degree of pain with quality of life osteoarthritis patients in Neurology Department Dr. Hardjono Hospital Ponorogo. Methods: This study used an observational analytical methods with cross sectional design. The sample were taken based on Purpossive Sampling methods from Neurology Department Dr. Hardjono Hospital Ponorogo. This data analyzed used Pearson Test. Result: Distribution from 40 responden consist of 24 woman's patients and 16 man's patients. The higest proportion of the age range is 45-54 years old. 18 patients have to impaired in Quality of Life. Based on Pearson analytic test showed there was significant correlation between degree of pain and quality of life in osteoarthritis patients p<0,0001 and correlation coefficients showedr= - 0,965 Conclusion: Increasing score degree of pain caused poor quality of life osteoarthritis patients in Neurology Department Dr. Hardjono Hospital Ponorogo.